Otimização da remoção da matéria carbonácea e nitrogenada do esgoto sanitário por reator anaeróbio e aeróbio de leito fixo - Belini, Aldria Diana (2016)
The increase in population worsens the quality of existing receiving bodies, because the concentration of sewage dumps with high organic and nitrogen loads. There are numerous processing operations, however, the application of biological processes, in most cases is the most economical alternative. Thus, this study aims to optimize the removal of carbonaceous and nitrogenous matter sanitary sewer system consists of a combined anaerobic and aerobic fixed bed reactor. The system was composed of anaerobic and aerobic fixed-bed reactors, with upward flow and continuous flow, rectangular base and useful volume of 19.8 L and 19.3 L, respectively, plus a solid liquid separation device with a volume of 7 3 L (HDT 8 h in each reactor) and 9.8 L (HDT 6 h in each reactor). The medium support for biomass immobilization consisted of corrugated rings Polyvinyl Polyvinyl (PVC). The system was operated in six different stages in which was varied the recirculation rate (50% step 1, 100% step 2 and step 3 150%) and flow aeration (step 4 10 L.min-1, Step 5 5 L .min-1 and step 6 2.5 L.min-1). For the evaluation system, it was determined the following physicochemical parameters: liquid temperature (TL), pH, total alkalinity (AT), bicarbonate alkalinity (AB), volatile acids (AV), dissolved oxygen (DO), chemical oxygen demand (COD) Total kjeldahl nitrogen (N-TKN), ammonia (N-ammonia), nitrite (N-NO2-), nitrate (N-NO3-) and phosphorus (P). The hydrodynamic behavior evaluation was performed by pulse type stimulus-response technique of injection of the dye Eosin Y. The results obtained in the first three steps with recirculation rate influence of variation (50%, 100% and 150%) showed removal concentration of organic matter in terms of COD (raw samples) greater than 97%, for nitrogen concentrations, the removal of N-TKN was greater than 95%; it was concluded that the higher the recirculation rate is nitrogen removal efficiency and lower the nitrite values and nitrate, however it is worth noting that increasing the recirculation rate causes an increase of OD concentration in the anaerobic reactor which may cause the imbalance of the process. To observe the influence of variation in the flow aeration with constant recirculation rate of 100%, the removal of organic matter showed a COD(raw samples) removal higher than 98% while the nitrogen removal fell as the reduction of aeration flow ( Qa) with N-TKN removal efficiencies exceeding 96% (Qa = 10 L.min-1), 90% (Qa = 5 L.min-1) and 45% (Qa = 2.5 L.min-1). And regarding the variation of TDH, in the removal of organic matter, obtained higher removal values DQO(raw samples) 98% (HDT of 8 hours in each reactor) and 99% (HDT of 6 hours in each reactor) while for nitrogen removal efficiencies were higher than 96% for both tested HDT which shows that the combined system showed a good ability to cushion the variation of hydraulic and organic fillers.